Integrated Approach to Study Spatial Variations in Water Resources: A Case Study of Chandraprabha Basin - Mishra, Kavita (National Geographical Journal of India, 2022)
An integrated approach in mapping and analysis of availability, utilization and conservation of water resources is urgently needed to fulfill the increasing demand of water for irrigation, human and livestock consumption, industries, hydro electric power generation, recreation and other consumptive uses. The approach comprehends the use of modern techniques of Remote Sensing (RS) and Geographic Information System (GIS) as well as traditional techniques and data sources for getting reliable and desired results. Revolution in the digital world has opened a new arena of mind-set in the field of geospatial mapping and analysis. As a result, the RS and GIS have provided very powerful data base and techniques of analysis for solving complex problems of resources inventory, hydrogeomorphic features, geomorphic hazards, environmental problems, geo-environmental management etc. Present paper attempts to assess the spatial variation in water resources using integrated approach taking into account a case study of Chandraprabha Basin which accounts a major portion of Karmanasha Basin (Eastern Uttar Pradesh). The interpretation of Remote Sensing (RS) data in conjunction with ancillary data and sufficient ground truth information makes it possible to identify and outline the presence of various surface and sub surface water resources. The study is largely based on the integrated use of data and techniques like RS and GIS along with the supportive information gathered from different sources.